Alexithymia and Relationship Dissatisfaction: The Role of Conflict Communication Patterns - Binti Zulkifli, Nur Aisyah; Chaiyasit, Kittipong; Gong, Jiaowei (Applied Family Therapy Journal (AFTJ), 2025)
Objective: To test a structural model in which alexithymia predicts relationship dissatisfaction both directly and indirectly through destructive conflict communication patterns among Malaysian adults. Methods and Materials: A descriptive correlational design was used with 423 adults in ongoing romantic relationships recruited across Malaysian states. Measures included the Toronto Alexithymia Scale–20 (TAS-20), the Communication Patterns Questionnaire (CPQ), and the Couples Satisfaction Index (CSI; reverse-scored to indicate dissatisfaction). Data screening confirmed statistical assumptions before analyses. IBM SPSS 27 was used for descriptive statistics and Pearson correlations, and AMOS 21 for structural equation modeling (SEM) with maximum likelihood estimation. Model fit was evaluated using χ², χ²/df, GFI, AGFI, CFI, TLI, and RMSEA; mediation was tested via indirect paths. Findings: Alexithymia correlated positively with destructive conflict communication (r = .56, p < .001) and relationship dissatisfaction (r = .48, p < .001); conflict communication correlated most strongly with dissatisfaction (r = .62, p < .001). The SEM demonstrated good fit: χ²(132) = 287.43, χ²/df = 2.18, GFI = .93, AGFI = .91, CFI = .96, TLI = .95, RMSEA = .053. Direct paths were significant from alexithymia → conflict communication (b = 1.12, β = .56, p < .001), alexithymia → dissatisfaction (b = 0.48, β = .29, p < .001), and conflict communication → dissatisfaction (b = 0.53, β = .48, p < .001). The indirect effect of alexithymia on dissatisfaction via conflict communication was significant (b = 0.59, β = .27, p < .001), yielding a total effect of β = .56 (p < .001), consistent with partial mediation. Conclusion: Alexithymia is a robust interpersonal risk factor for relationship dissatisfaction, and its impact is partly transmitted through destructive conflict communication. Findings highlight dual intervention targets—enhancing emotional awareness and improving conflict-management skills—to mitigate dissatisfaction in intimate relationships within a multicultural Malaysian context.